2005
DOI: 10.1016/j.pec.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of work-related and personal factors in diabetes self-management

Abstract: The aim of this study was to investigate how factors in the workplace and personal factors are related to the frequency with which people with diabetes perform self-management activities and the degree to which they do or do not experience the performing of self-management activities as a burden. Two hundred and ninety-two employees with insulin-treated diabetes completed questionnaires on socio-demographic and illness-related background variables, work experience, diabetes self-efficacy, social support outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 22 publications
8
68
0
3
Order By: Relevance
“…The predictability of self-efficacy has been demonstrated for several diabetes self-care behaviors [35][36][37], but changes in self-efficacy behavior have not typically been included in physical activity intervention studies on individuals with type 2 diabetes [38]. However, physical activity self-efficacy (both "Making time" and "Resisting relapse") significantly increased at 8 weeks and 6 months after a behavioral intervention targeting physical activity in individuals with type 2 diabetes (N = 358); these changes were not significantly different at 1 year [39].…”
Section: Discussionmentioning
confidence: 99%
“…The predictability of self-efficacy has been demonstrated for several diabetes self-care behaviors [35][36][37], but changes in self-efficacy behavior have not typically been included in physical activity intervention studies on individuals with type 2 diabetes [38]. However, physical activity self-efficacy (both "Making time" and "Resisting relapse") significantly increased at 8 weeks and 6 months after a behavioral intervention targeting physical activity in individuals with type 2 diabetes (N = 358); these changes were not significantly different at 1 year [39].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal research is required to corroborate these relationships. Both Weijman et al [25] and Munir et al [41] found that outside support was a better predictor for self-management behaviors than workplace support. Future studies should include these measures in order to better detect the relationship between support and self-management, and compare the relative contribution of work and non-work support to illness self-management.…”
Section: 41]mentioning
confidence: 95%
“…Very few studies have examined the influence of work conditions and self-efficacy on self-management of illness at work [24,25]. Weijman et al [25] found that employees were able to manage their diabetes in the workplace more effectively if they had high self-efficacy and were able to control their workload, working hours and work pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Multidimensional Diabetes Self-management Checklist (MDSC) [25] measures four domains of self-management activities for individuals with insulin-treated diabetes: (1) dietary self-management (following dietary guidelines, eating regularly); (2) injecting insulin (the recommended frequency, the recommended dosage of insulin); (3) blood-glucose monitoring; (4) adjusting the insulin dosage to specific circumstances. These four self-management activities have been selected because they may be difficult to plan for and interfere with one's daily routines.…”
Section: Diabetes Self-management Activitiesmentioning
confidence: 99%